Клиническая оценка эффективности применения современных композиционных материалов в восстановительной терапии жевательной группы зубов (Эндодонтия Today)
In article the data of the modern literature about methods and materials for regenerative therapy of firm fabrics of tooth are cited. Application of modern composite materials urged to help with increase of efficiency of treatment of caries. The comparative estimation of efficiency to application of composite materials on a basis methacrylate and silorane matrixes is spent in regenerative therapy of firm fabrics of tooth at caries treatment in the nearest and remote terms of supervision with traditional methods of treatment. The data of clinical researches of 108 patients who were under supervision within 24 months at which it has been cured 120 chewing teeth concerning caries are processed. The comparative estimation of the remote results of a condition of available seals on the basis of recommendations FDI about criteria G. Rage. Results of clinical researches have shown that the modern material on silorane basis Filtek Silorane for restoration of chewing group of teeth by the basic criteria of an estimation of seals in the remote terms of supervision has considerably best indicators, than materials on a basis methacrylate Filtek P60 and QuiXfil.